CHARACTERISTICS OF INDONESIAN HOUSEHOLD’S LIVING EXPENDITURE - Donna, Duddy Roesmara (Universitas Negeri Semarang, 2014)
The aim of this study is to estimate and analize the characteristics of Indonesian household expenditure on goods and services, for example food, clothes, household utensils, housing, medical care, education, oil and transportation, gas, electricity and communication. Linear Expenditure System (LES) model and seemingly uncorrelated regression (SUR) estimation method were applied. This study has some conclusions. First, if ones have more incomes, they will proportionally allocate them for housing, oil and transportation, education, food, and medical care. Second, medical care, education and communication are categorized as superior or deluxe commodities. Third, the approximation of minimum living expenditure to survive is Rp 147.236 for a household per week.Â Â